Dampak Penerapan Corporate Social Responsibility (CSR) dan Karakteristik Bank Pada Kinerja Perbankan - Albaasith, Shooma Fikri; Mawardi, M. Cholid; Fakhriyyah, Dewi Diah (Universitas Islam Malang, 2024)
The purpose of this research is to find out and analyze how the influence of Corporate Social Responsibility and bank performance affects the performance of banks listed on the Indonesia Stock Exchange and the Financial Services Authority. This research uses a quantitative approach. The research location was carried out on banking companies listed on the Indonesia Stock Exchange and the Financial Services Authority for the period 2019-2022 on the pages www.idx.go.id and https://www.ojk.go.id/en/Default.aspx. Sampling was done based on the purposive sampling method with predetermined criteria resulting in 52 samples. The results of the study state that Corporate Social Responsibility has a positive effect on the bank's financial performance, but does not affect the bank's non-financial performance. As for bank characteristics, it has a positive effect on the bank's financial and non-financial performanceKeywords: corporate social responsibility and bank characteristics